2000
DOI: 10.1002/(sici)1097-0096(200005)28:4<194::aid-jcu8>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal sonographic detection of pericardial teratoma

Abstract: Patients with pericardial teratomas usually present shortly after birth with cardiorespiratory distress or in utero with hydrops fetalis. We report a case in which the tumor was diagnosed in utero using sonography during a routine obstetric examination. Sonograms showed a 3‐cm echogenic mass compressing the right atrium. The lesion was inhomogeneous with solid and cystic areas. The fetus was followed to term, and additional radiologic studies were performed before the infant underwent surgery. Prenatal identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…In the comprehensive review of Bustamante et al 1 , 15 cases of IPT diagnosed in utero were reported. A review of the English and Spanish medical literature added further cases that were documented later 2 -7 , and, at the time of writing, ours was the 25 th case (Table 1; refs 2 -22 ).…”
Section: Fetal Intrapericardial Teratomamentioning
confidence: 99%
See 2 more Smart Citations
“…In the comprehensive review of Bustamante et al 1 , 15 cases of IPT diagnosed in utero were reported. A review of the English and Spanish medical literature added further cases that were documented later 2 -7 , and, at the time of writing, ours was the 25 th case (Table 1; refs 2 -22 ).…”
Section: Fetal Intrapericardial Teratomamentioning
confidence: 99%
“…Tollens et al reported the presence of a second tumor in the superior mediastinum 19 . Differential diagnosis should include other thoracic masses such as pulmonary masses, bronchogenic cyst, intracardiac neoplasms, mediastinal teratoma and ventricular aneurysms 1,8,9,15,20 . The presence of pericardial effusion should alert one as to the possibility of IPT.…”
Section: Fetal Intrapericardial Teratomamentioning
confidence: 99%
See 1 more Smart Citation
“…The multicystic nature, large size, and combination of adipose tissue and calcification within the mass are suggestive of teratoma. Bustamante et al 8 stressed that radiologists should leave the diagnosis open concerning other pericardial masses such as bronchogenic cysts, cystic hygroma, hemangioma, and mesothelioma in differential diagnosis of these cases. Differential diagnosis between pulmonary sequestration and teratomas or other intrapericardial masses may not be possible until after histopathologic examination.…”
mentioning
confidence: 95%
“…In the fetus and the neonate, intrapericardial teratomas are detected using two-dimensional echocardiography. Diagnosis may be confirmed by MRT or computer tomography [2,5]. This is the first report on the use of 3D-echocardiography for diagnosis and evaluation of a pericardial teratoma.…”
mentioning
confidence: 99%